Microwave Radiation Applied to the Synthesis of -butyrolactone Derivatives - Paulo Marcos Donate; Hugo Elias Barbosa (Orbital: The Electronic Journal of Chemistry, 2021)
Many natural products with a broad spectrum of biological effects bear the g-butyrolactone ring. Given the difficulty in isolating large amounts of butyrolactones from natural sources, interest in synthesizing structural analogs of these compounds and in studying their biological properties has increased. In this review, we summarize the main synthetic methodologies to construct γ-butyrolactone derivatives by using multicomponent processes.